Netvista Public Wireless Network Quality Analysis Using Quality Of Service Parameters - Putra, Fauzan Prasetyo Eka; Ubaidi, Ubaidi; Mayangsari, Dwi; Hasanah, Nor (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The use of public wireless networks is increasingly used by the public because it is able to touch all walks of life using the internet because of its affordable prices. Apart from the affordable price, the ease of accessing this network so that many people prefer to take advantage of public wifi. However, with the increasing number of network users, of course, it will affect the quality of the network. Based on these problems, the researcher decided to conduct a study to analyze the quality of the public wireless network from NETVISTA. The NETVISTA public wireless network can be accessed in Kangenan Gg. 1, so the researcher decided to conduct research at the location for 2 days. This study aims to determine the quality of the internet connection network based on QoS parameters by knowing the delay, throughput, and packet loss obtained from the axence nettols application which will later be compared with the TYPHON standard so that the quality of the NETVISTA public wireless network can be known. The method used in this study is descriptive analysis. From this study, the results were obtained that many users (category: